O envelhecimento humano na formação de educadores - Pastorio, Anapaula (2020)
Population aging cannot be neglected by society, which urgently needs to adapt to this new age context, in which the elderly population increases exponentially, and their demands. This dissertation was developed with the general objective of investigating the implementation of the Transversal Topics for Teacher Training I course, which took place in 2019 at the Federal University of Santa Maria (UFSM). This dissertation was divided into two articles. The first presents an integrative review with the objective of identifying, based on the literature, references found in the online research platforms, Latin American and Caribbean Center for Health Sciences Information and Scientific Electronic Library Online, as gerontology has been addressed in the educational context of Universities. The second manuscript deals with the implementation of the Transversal Topics for Teacher Training I course in UFSM undergraduate courses, in the light of the guidance proposed by the Ministry of Education (MEC) in Resolution No. 02/2015, which brings with it the transversal theme : age groups, in order to accompany the adaptation of Higher Education - in this case UFSM - to the current social age context. As a result, the integrative review shows that the manuscripts in general are limited to describing the creation of undergraduate courses in gerontology, such as the Federal University of São Carlos, Pontifical Catholic University (PUC-SP), University of São Paulo (USP) and / or characteristics of bachelor's gerontologists. The second article deals with the recognition of the merits of UFSM by proposing itself as a pioneering institution with regard to the adequacy of higher education to the Resolution proposed by MEC, referring to the development of transversal themes in support of respect for social diversity initially in undergraduate courses. Finally, in general, it should be stressed that efforts must be made so that higher education prepares future professionals in a manner consistent with the social reality, in which knowledge in the gerontological area is absolutely necessary.